Si-GEMAS: Serious game mathematical crossword puzzle learning media for students critical thinking ability - Cholily, Yus Mochamad; Darmayanti, Rani; Lovat, Terence; Choirudin, Choirudin; Usmiyatun, Usmiyatun; Muhammad, Ilham (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Critical personality is a skill that must be possessed in order to survive in the global competition of 21st-century society. Given that critical thinking education is an essential part of human life, innovations must be carried out to foster students' critical thinking. One of his studies was the innovation of crossword learning media (Si-GEMAS). This study aimed to develop Si-GEMAS learning media for the mathematical critical thinking skills of Grade VIII SMP students at YALCP Pasuruan, which are valid, practical, and effective in the learning process. This is intended to determine its validity and efficiency. This research specialty was based on the Borg n Gall development model. The research subjects were ten students of class VIII. The instruments used were validation sheets, teacher and student response questionnaires, and student learning outcomes tests. The results showed that the relevance score of Si-GEMAS learning media with students' critical thinking skills was in the very valid category and efficient. It shows that the Si-GEMAS media was valid and efficient. It increases students' critical thinking from an average of 65.67 to 88.28. It shows that there is an increase of 22.61. So it can help students develop critical thinking skills in learning.